Are Psychiatrists Trained to Address the Mental Health Needs of Young People Transitioning From Child to Adult Services? Insights From a European Survey - Russet, Frederick; Humbertclaude, Veronique; Davidovic Vrljicak, Nikolina; Dieleman, Gwen C.; Dodig-Ćurković, Katarina; Franic, Tomislav; Gerritsen, Suzanne E.; de Girolamo, Giovanni; Hendrickx, Gaelle; Kerbage, Hala; McNicholas, Fiona; Maras, Athanasios; et al. (Frontiers in Psychiatry, 2022)
Background: In mental health, transition refers to the pathway of young people from child and adolescent to adult services. Training of mental health psychiatrists on transition-related topics offers the opportunity to improve clinical practice and experiences of young people reaching the upper age limit of child and adolescent care. Methods: National psychiatrists’ organizations or experts from 21 European countries were surveyed 1/ to describe the status of transition in adult psychiatry (AP) and child and adolescent psychiatry (CAP) postgraduate training in Europe; 2/ to explore the amount of cross-training between both specialties. This survey was a part of the MILESTONE project aiming to study and improve the transition process of young people at the service boundary. Results: Transition was a mandatory topic in the AP curriculum of 1/19 countries (5%) and in the CAP curriculum of 4/17 countries (24%). Most topics relevant for transition planning were addressed during AP training in 7/17 countries (41%) to 10/17 countries (59%), and during CAP training in 9/11 countries (82%) to 13/13 countries (100%). Depending on the training models, theoretical education in CAP was mandatory during AP training in 94% (15/16) to 100% of the countries (3/3); and in AP during CAP training in 81% (13/16) to 100% of the countries (3/3). Placements were mandatory in CAP during AP training in 67% (2/3) to 71% of the countries (12/17); and in AP during CAP training in 87% (13/15) to 100% of the countries (3/3). Discussion and Conclusion: Specific training about transition is limited during CAP and AP postgraduate training in Europe. Cross training between both specialties offers a basis for improved communication between child and adult services but efforts should be sustained in practical training. Recommendations are provided to foster further development and meet the specific needs of young people transitioning to adult services.